Islamic Law Analysis of the Prosecutor's Authority in Asset Forfeiture from Corruption - Utama, Budi; Angkasa, Angkasa; Prayitno, Kuat Puji; Sudrajat, Tedi; Najib, Muhammad Ainun (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2025)
Efforts to recover assets resulting from corruption remain hindered by legal loopholes and concealment strategies, especially when offenders register illicit assets under the names of third parties. This study explores how prosecutors perceive the legitimacy of such assets and their views on the necessity of reforming Indonesia’s asset forfeiture framework. Using a qualitative empirical design, the research is based on semi-structured interviews with four prosecutors who have handled corruption cases involving complex asset ownership. The findings reveal that prosecutors consistently view these assets as materially and morally illegitimate, even if formally registered under others' names. They also support introducing a non-conviction-based asset forfeiture (NCBAF) model to overcome the limitations of conviction-dependent mechanisms, especially in cases where suspects die or flee. Islamic legal principles, such as the ḥifẓ al-māl (preservation of wealth) and taʿzīr bi al-māl or discretionary penalties targeting unlawfully acquired assets, offer a moral and doctrinal basis for such reforms. These insights contribute to ongoing legal debates and support the development of a more effective and ethically grounded policy for asset recovery in corruption cases.